Implementation of ancient manuscript collection preservation through digitization methods at The Widya Pustaka Library of Pura Pakualaman Yogyakarta - Prasasti Cahya; Andriyana Fatmawati (Daluang: Journal of Library and Information Science, 2026)
Purpose. This study aims to examine how the preservation of ancient manuscript collections is implemented through digitization methods. Methodology. The study uses a qualitative research method with a descriptive approach, where data is obtained through observation, interviews, and documentation. Results and discussion. The results of the study show that the Widya Pustaka Library carries out the digitization process through three main stages, namely the pre-digitization, the digitization stage, and the post-digitization stage. In its implementation, challenges were encountered, particularly in the pre-digitization stage (lack of a dedicated studio, no written guidelines on the equipment used, and no standardization of metadata file naming), the digitization stage (no written SOPs or technical guidelines, damaged or tightly bound manuscripts, lighting, manual editing process), the post-digitization stage (digitization results not yet available online), and other challenges such as limited funding. These findings indicate that successful manuscript digitization depends not only on technical equipment but also on standardized procedures and institutional support. Furthermore, improving documentation standards and online access would enhance both the preservation and utilization of digitized manuscripts. Conclusions. Digitization is an effective strategy for preserving ancient manuscripts at the Widya Pustaka Library because it maintains the authenticity of the content while increasing access without physically handling the fragile manuscripts. Despite several technical challenges, the digitization process remains a crucial step in preservation efforts and can serve as a reference for other institutions with similar collections.